Mineral trioxide aggregate as material of choice in endodontic therapy - Jokanović Vukoman; Čolović Božana; Živković Slavoljub; Živojinović Vesna; Marković Dejan (Serbian Medical Society - Dental Section, Belgrade, 2011)
Mineral trioxide aggregate (MTA) is a material with broad indications in endodontics. Currently, this material is used for pulp capping, pulpotomy, as apical barrier in teeth with necrotic pulp and open apex, and in the treatment of various root canal perforations. By comparing the biological response of pulp tissue capped with calcium hydroxide and MTA, the superiority of MTA has been indicated. The bridge of hard tissue formed under MTA prevented the irritation of pulp. Histological studies of pulpotomy in dog teeth have shown after 120 days a hard tissue without necrosis formed under MTA. MTA is also the material of choice for retrograde root canal obturation and lateral perforation. Meta analysis of published papers on MTA in recent years indicated the great clinical success of this material which ensured a good canal seal and superior biocompatibility. It is the only material for retrograde root canal obturation that encourages tissue regeneration. Studies have also shown that MTA has inductive and conductive properties for hard tissue as well as the ability to release ions in a liquid medium. The main disadvantage of MTA is related to its color, the presence of iron and mangan ions, the difficulties in maintaining the characteristics of material during time, absence of solvent for this material and the difficulty for its removal after crosslinking.